2023
DOI: 10.1111/epi.17647
|View full text |Cite
|
Sign up to set email alerts
|

Integrated psychological care services within seizure settings: Key components and implementation factors among example services in fourILAEregions: A report by theILAEPsychiatry Commission

Milena Gandy,
Rosa Michaelis,
Jayne Acraman
et al.

Abstract: Mental health comorbidities are prevalent and problematic in patients with seizures but often suboptimally managed. To address common gaps in care, the Integrated Mental Health Care Pathways Task Force of the International League Against Epilepsy (ILAE) Psychiatry Commission was tasked with providing education and guidance on the integration of mental health management (e.g., screening, referral, treatment) into routine seizure care. This report aims to describe a variety of established services in this area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It is also recommended to identify the underlying causes of epilepsy and its comorbidities (Figure 1). 2,7,8 Despite the development of new drugs for treating epilepsy, one‐third of patients still experience seizures; therefore, epilepsy remains a worldwide critical public health concern 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also recommended to identify the underlying causes of epilepsy and its comorbidities (Figure 1). 2,7,8 Despite the development of new drugs for treating epilepsy, one‐third of patients still experience seizures; therefore, epilepsy remains a worldwide critical public health concern 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…It is also recommended to identify the underlying causes of epilepsy and its comorbidities (Figure 1). 2,7,8 Despite the development of new drugs for treating epilepsy, one-third of patients still experience seizures; therefore, epilepsy remains a worldwide critical public health concern. 9,10 Central nervous system (CNS) cancer is the seventh most common tumor in adults and constitutes 25% of malignant tumors in children; it is also the second leading cause of cancer-related death in young people.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the recurrent and unpredictable nature of epilepsy, patients with epilepsy experience psychological symptoms more frequently than the general population and individuals with other chronic diseases ( 1 , 2 ). For instance, anxiety disorders are highly prevalent as psychiatric comorbidities in epilepsy ( 3 ), with an average prevalence of 32.6% for clinically significant anxiety symptoms among individuals newly diagnosed with epilepsy ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…One way to address the increased mental health needs of this population is through targeted services available as part of a multidisciplinary clinic (Samanta et al, 2021), and the International League Against Epilepsy has also provided support and guidance on developing such service lines (Gandy et al, 2023). Past research has demonstrated that integration of psychosocial services into pediatric epilepsy clinics is both feasible and necessary, given psychosocial risks discussed at length above including increased risks for depression and suicidality (Guilfoyle et al, 2013(Guilfoyle et al, , 2015.…”
mentioning
confidence: 99%